Embracement with risk classification: opinion of the nurses at an emergency service - Kelly Karine Sales Zem; Juliana Helena Montezeli; Aida Maris Peres (Rev Rene)
This study aimed to identify the understanding of nurses from an emergency service on humanization and their conception on the embracement with risk classification. Descriptive qualitative research carried out from July to September 2010 through semi-structured interview with eight nurses from an emergency service of a school hospital in Curitiba, Parana, Brazil. The data underwent Bardin's content analysis. Three categories emerged: the first describes the understanding of the nurses from the emergency service on humanization; the second, the understanding of these nurses on embracement with risk classification is shown; and the third, the essential elements for the implementation of embracement with risk classification are listed. There is a need for the subjects to deepen their knowledge on the recommendations from the National Politics of Humanization to implement the embracement with risk classification in this scene.